The phytosanitary situation of cypress in Spain and the new prospect - Tuset, Juan J. (Comitato Nazionale per le Scienze Agraria, Regione Toscana (CNR), 2023)
The cypress (Cupressus spp.) and its most important species (C. sempervirens L.) is of rather recent introduction in Spain. The oldest trees are not more than 160-180 years of age and the early (and widest) dispersion was almost exclusively confined to the religious grounds (monasteries, hermitage roads, graveyards, etc.), and, also, in private and public gardens. lt is a normal seeing to meet throughout the Spanish geography cypress rows growing alongside of the narrow and zigzag roads leading to a white hermitage, monastery, convent or calvary and also, the dark green colour of these trees with a cone type crown (it is majority the fastigiate from), exceeding above the graveyards walls. This landscape is, in most cases, a typical Spanish identity symbol for foreign visitors (TUSET, 1990). Later, at the end of the XIX century, the common or Italian cypress (C. sempervirens) came into usage as windbreaks ornamental hedges, and country house boundaries. It is only 40 years ago since this species has been incorporated as auxiliary plant in new reafforesttions of pine trees. For these reasons, it is not possible to find large (or small) areas populated by this interesting species in Spain. Its usage is increasing at present, specially in ornamental horticulture (Tuset, 1990). The most important cypress species present in Spain are: C. sempervirens under both fastigiata (the more abundant) and horizontalis forms, and C. arizonica Greene, C. macrocarpa Hartw., C. glabra Sudw, and C. lusitanica Mill. (some trees of the latter one growing in the Atlantic coast) are also present, generally in gardens as ornamental trees. The small areas of expansion of the cypress together with the common low environmental moisture clearly condition the pathological problems, generally limiting their importance (TUSET, 1979). Anyway, we have emphasized during the last decade the study of the cypress diseases occurring in Spain, starting a research program at the Mycology Department of the IVIA..